Open-cell foams coated by Ni/X/Al hydrotalcite-type derived catalysts (X = Ce, La, Y) for CO2 methanation. Issue 42 (December 2020) - Ho, Phuoc Hoang; Sanghez de Luna, Giancosimo; Ospitali, Francesca; Fornasari, Giuseppe; Vaccari, Angelo; Benito, Patricia
Graphical abstract: Highlights: Open-cell foams coated catalysts derived from hydrotalcite-type compounds promoted by La, Y, Ce Outstanding CH4 production rates (6.75–8.35 mole gNi −1 h −1 ) for CO2 methanation NiCeAl on NiCrAl foam highly active at low temperature and high space velocity Higher conversion and selectivity on NiCeAl foam than pellet bed at similar outlet temperature Abstract: NiAl hydrotalcite-type materials containing rare-earth elements (La, Ce, Y) are coated on thermal conductive NiCrAl open-cell foams by the electrodeposition method. After calcination and reduction at 600 °C, the obtained structured materials have a stable coating wherein Ni nanoparticles are well-dispersed. Consequently, the catalysts with rare-earth elements show a remarkable activity enhancement in the CO2 methanation in comparison to a NiAl catalyst. At 325 °C (oven temperature) CH4 productivity rates of 6.75–8.35 mole gNi −1 h −1 (38, 200 h −1, CO2 /H2 /N2 = 1/4/1 v/v) are achieved. Ce has the largest effect on the improvement of the CO2 conversion and stability (also feeding a N2 free feedstock) followed by Y and La, due to the balance between the amount and activity of the catalytic coating. The Ce structured catalyst is also more active and selective than its pelletized counterpart at similar outlet temperature. Temperature profiles recorded along the centerline of the catalytic bed provide an overview of hotspot formation that plays an important role in the control of activity/selectivity and catalyst deactivation.